– Islamic formulas and their role in reducing the risks of financing –Applied Study on Faisal Islamic Bank of Sudan - Al Huda, Yousef Ahmed Yousef; Akbar, Hamza Bshri Jumaa (Journal of Economic, Administrative and Legal Sciences, 2019)
The problem of research was that the application of Islamic formulas would reduce the risk of financing and help the Islamic formulas in the optimal use of invested funds to make the projects successful and prevent the dealing with the profit that causes economic crises as well as their contribution to achieving economic, social and human development within the framework of legal standards. To the definition of the concept and variance in Islamic formulas and the difference between them and other forms of financing and the possibility to identify the application of Islamic financing formulas in accordance with the principles of Islamic law, and identify the forms of Islamic finance, which are important in providing accounting information For investors, the research followed the historical method to track the previous studies related to the subject of the study, the deductive approach to determine the dimensions of the research problem, the inductive approach to the selection of research hypotheses, the analytical descriptive approach to the case study and the research reached several results, including the existence of legitimate control in the application of Islamic formulas when granting funding leads to Reducing the risk of financing and familiarity with the provisions of credit transactions in Islamic Shari'ah limits the risk of financing. The use of Islamic formulas by the investors reduces the risks related to financing. The research recommends the following recommendations: Islamic financing formulas in banks and financial decision makers rely on the accounting information provided by Islamic formulas and the applicants must avoid funding provided by non-Islamic formulas, as this increases the risk of financing and helps spread the severity of economic crises and the need to develop the employment of Islamic formulas to keep up with development Which occurred in information technology.
Keywords: Islamic formulas; financing risks; financing grants; credit transactions; financing decisions